2020
DOI: 10.3390/ma13194319
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Rice Husk Ash as Supplementary Cementitious Material after Production in the Field and in the Lab

Abstract: Supplementary cementitious materials (SCM) can reduce the total amount of Portland cement clinker in concrete production. Rice husk ashes (RHA) can be converted from an agricultural by-product to a high-performance concrete constituent due to a high amount of reactive silica with pozzolanic properties if they are burnt under controlled conditions. The way and duration of combustion, the cooling process as well as the temperature have an effect on the silica form and thus, the chemical and physical performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…Moreover, the grinding time affects the final pozzolanic performance remarkably, as higher surface area values of the ash lead to more reactive sites for a pozzolanic reaction. Similar trend was observed by Thiedeitz et al [ 72 ].…”
Section: Test Results and Discussionsupporting
confidence: 91%
“…Moreover, the grinding time affects the final pozzolanic performance remarkably, as higher surface area values of the ash lead to more reactive sites for a pozzolanic reaction. Similar trend was observed by Thiedeitz et al [ 72 ].…”
Section: Test Results and Discussionsupporting
confidence: 91%
“…RHA Composition, Applicability and Effects Study by Thiedeitz et al [5] indicated specific surface area based on BET adsorption method for rice husk ash (grounded for 20 seconds with 20 Hertz frequency) and cement CEM 1 42.5R were 128 m 2 /g and 1.24m 2 /g respectively. Study by Fernandes et al [33] on RHA from thermoelectric company in Brazil, indicated mean diameter of 19.56 + 0.49 µm, specific weight of 2.22 + 0.0028 g/cm 3 and specific area of 11.35 + 0.21 m 2 /g, for RHA described in table 1.…”
Section: 1mentioning
confidence: 99%
“…Study by Thiedeitz et al [5] generally 40% cement replacement with RHA or fly ash indicated strong reduction of compressive strength, whereas 20% cement replacement with RHA or fly ash could even improve performance. Study by Sala et al [6] for 10% replacement by weight of metakaolin, thermal RHA and chemical treated rice ash with raw materials from Colombia indicated that pozzolanic material incorporation increased concrete compressive strength.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In another work, Franceschini et al prepared covalently bonded polymer C–S–H composite with the formation of covalent linkages between polymer and C–S–H phases by grafting trialkoxysilane (T-silane) and methyldialkoxysilane (D-silane) to the polymer chains [ 19 ]. To sum up, there are some attempts for the development of cement mixes by using rice husk ash as an alternative additive and direct or partial replacing with silica [ 20 , 21 , 22 , 23 ] and also most of the published works are mostly focused on the enhancement of strength properties of cementitious composites [ 24 , 25 ]. Besides, the effect of functionalized RHA by silane coupling agents on thermal and mechanical properties of thermoplastic composites was investigated to improve interfacial interactions in the composite structure [ 26 ].…”
Section: Introductionmentioning
confidence: 99%